Vitreous Hyper-Reflective Dots in Optical Coherence Tomography and Retinal Tear in Patients with Acute Posterior Vitreous Detachment. (3rd August 2017) - Oh, Jong-Hyun; Oh, Jaeryung; Roh, Hyun Cheol
ABSTRACT: Purpose : To report the presence of hyper-reflective dots in the vitreous cavity using spectral-domain optical coherence tomography (SD-OCT) in patients with acute symptomatic posterior vitreous detachment (PVD) and investigate their association with the presence of retinal tear. Methods : The medical records of 77 patients with acute symptomatic PVD, who were examined between March 2013 and February 2015, were reviewed. The severity of vitreous hyper-reflective dots (VHDs) was graded using SD-OCT images, and the presence of retinal tear was assessed. Results : Forty-one (53.2%) eyes had mild VHDs, 13 (16.9%) eyes had moderate VHDs, and 14 (18.2%) eyes had severe VHDs. Retinal tear was found in 21 (27.3%) eyes. The presence of severe VHDs was associated with an increased likelihood of retinal tear (positive likelihood ratio, 9.78; 95% confidence interval, 3.02–31.63). In 14 (66.7%) eyes with retinal tear, the mean number of VHDs significantly decreased from 23.2 ± 20.27 to 2.3 ± 2.66 at a mean follow-up interval of 2.8 ± 1.48 weeks (P = 0.002). Conclusions : The presence of severe VHDs is suggestive of retinal tear in patients with acute symptomatic PVD. However, this SD-OCT finding should be limited to the acute phase of PVD.